Pemetaan Persebaran Nasabah Kredit Macet Perusahaan Multifinance: Studi Kasus PT. XYZ Cabang Salatiga - Zusrony, Edwin; Kuncoro, Wreda; Nurrochman, Nurrochman (Universitas Nusantara PGRI Kediri, 2018)
A financing company is a business institution that runs financing activity in procurement of goods and or services (POJK No. 29/2014). Financing company development in urban area, especially in Salatiga area has been experiencing great progress, as a numerous financing companies have opened their branches in Salatiga. The research aims to classify PT. XYZ Finance Salatiga branch customer distribution by using Geographical Information System that it is practical for the company to determine potential market in order to grow the number of potential customer. Within the research there are GIS activity steps that cover arranging spatial and non spatial demography data of Salatiga and customers distribution region’s description in Salatiga. Bad credits distribution in PT. XYZ Salatiga branch has its biggest percentage in Argomulyo district that almost reach 51% from total credit plafond (outstanding principal) given. The research result will be able to help the company to make business decision related to determining the eligibility of prospective customers.